Measuring Internet Slang Style in the Marketing Context: Scale Development and Validation - Liu, Shixiong; Wu, Yi; Gong, Wu (Frontiers in Psychology, 2022)
Internet slang, as an emerging language variant, has been extensively used by practitioners in advertising and other communication activities. However, its unique characteristics that differ from standard language have yet to be explored. Drawing upon interdisciplinary theories on schema and communication styles, this research makes the first attempt to conceptualize and measure these characteristics by introducing a new multi-dimensional construct “Internet slang style” in the marketing context. It develops and validates a new scale to measure Internet slang style along the dimensions of amiability, overtness, candor, and harshness through a series of in-depth interview, survey, and experiment to real consumers. In addition, this research investigates the impact of Internet slang styles on brand personality and brand attitude. The results indicates that different Internet slang style dimensions positively correspond to different brand personality dimensions, but exert no influence on brand attitude. Practically, the scale provides an easy-to-use instrument to evaluate Internet slang styles from a consumer perspective, so as to help companies appropriately employ Internet slangs in marketing communication activities.